Rancangan Aplikasi Sistem Pakar Diagnosa Penyakit Pankreatitis Dengan Metode Certainty Factor - Elvira Frisca Nasution (JURIKOM (Jurnal Riset Komputer), 2019)
Indonesia is one of the countries with the highest number of people with internal medicine. One of the many internal diseases suffered by people is pancreatitis. Pancreatitis is an inflammatory disease or inflammation of the pancreas which is generally caused by alcoholic beverages. The high increase in the number of sufferers of this disease has caused the need for medical personnel to increase. But the number of medical personnel such as experts in internal medicine is currently still low. Therefore researchers designed a system that could be used to help experts. Expert system is a system that can be used to help experts. This system is made like an assistant by adopting knowledge from experts. The expert system is able to diagnose the disease by providing value for each symptom. One method that is widely used in designing expert systems is the Certainty Factor method. The Certainty Factor method is very suitable to be used to measure the certainty of disease based on the value of hypothesis and evidence. The results of this study are the formation of an expert system application design that is able to diagnose pancreatitis based on symptoms chosen by the user